2019
DOI: 10.1136/bcr-2019-229815
|View full text |Cite
|
Sign up to set email alerts
|

Unduly long left main (79 mm) coronary artery arising from right coronary sinus in a 64-year-old diabetic man

Abstract: Coronary artery anomalies are usually an incidental finding on coronary angiogram. Most of them are benign, although few of them are malignant which may cause sudden cardiac death. A 64-year-old diabetic, hypertensive man underwent coronary angiography for evaluation of exertional dyspnoea, and angina which revealed an anomalous left main coronary artery (LMCA) arising from right coronary sinus which was unduly long (79 mm) but free from any disease. To the best of our knowledge after extensive search in liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Previous studies in patients with normal anatomy have reported a LM-length ranging from 10 to 15 mm and a bifurcation angle from 75.5°to 94°, while a LMlength > 15 mm was characterized as long. [15][16][17] Our findings are in line with these reports while in the cohort of patients with aberrant LCx, LM-length and bifurcation angle was measured longer and more acute when compared with normal anatomy. Measurements show excellent reproducibility and are easy to perform using the relevant workstation software which is readily available in the majority of catheterization laboratories across the world.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies in patients with normal anatomy have reported a LM-length ranging from 10 to 15 mm and a bifurcation angle from 75.5°to 94°, while a LMlength > 15 mm was characterized as long. [15][16][17] Our findings are in line with these reports while in the cohort of patients with aberrant LCx, LM-length and bifurcation angle was measured longer and more acute when compared with normal anatomy. Measurements show excellent reproducibility and are easy to perform using the relevant workstation software which is readily available in the majority of catheterization laboratories across the world.…”
Section: Discussionsupporting
confidence: 91%
“…The present study sought to identify practical angiographic parameters, in particular, LM‐length and the bifurcation angle, for the timely identification of an aberrant LCx. Previous studies in patients with normal anatomy have reported a LM‐length ranging from 10 to 15 mm and a bifurcation angle from 75.5° to 94°, while a LM‐length > 15 mm was characterized as long 15–17 . Our findings are in line with these reports while in the cohort of patients with aberrant LCx, LM‐length and bifurcation angle was measured longer and more acute when compared with normal anatomy.…”
Section: Discussionsupporting
confidence: 90%
“…Coronary anomalies are de ned as variations in their origin, trajectory, intrinsic anatomy, anastomosis and/or termination of the coronary arteries (Kayalar et al, 2009). Initially, they were considered a benign nding of coronary angiography (CACG) (Barriales et al, 2001;Luchessi et al, 2011;Palmieri et al, 2017;Sinha et al, 2019) or were diagnosed incidentally during autopsy (Hosoda et al, 2020). Their incidence according to the literature is 0.17 The objective of this study is to determine the incidence of anomalies and anatomical variants in their origin and proximal trajectory of the coronary arteries in the cadaveric population of the Departamento de Anatomía, Facultad de Medicina, Universidad de la República, Montevideo, Uruguay.…”
Section: Introductionmentioning
confidence: 99%